Phylogeny and Diversity of the Genus Pseudohydnum (Auriculariales, Basidiomycota) - Hong-Min Zhou; Hong-Gao Liu; Genevieve M. Gates; Fang Wu; Yu-Cheng Dai; Jerry A. Cooper (Journal of Fungi, 2022)
The toothed jelly fungus Pseudohydnum gelatinosum was originally described from Europe. The name has a broad sense and the species has been widely reported almost all over the world. We have studied samples of so-called P. gelatinosum from Asia and Oceania. Based on morphology, hosts, geography, and phylogenetic analysis using the internal transcribed spacer regions (ITSs) and the large subunit of nuclear ribosomal RNA gene (nLSU), four new species, P. himalayanum, P. orbiculare, P. sinogelatinosum, and P. tasmanicum, from China, New Zealand, and Australia are described and illustrated, and a new combination, Pseudohydnum totarae, is proposed. The five new taxa can be differentiated by the shape of their basidiomata, pileal surface color when fresh, spine size, basidiospore dimensions, shape of hyphidia, hosts, and biogeography. Phylogenetically, most of these taxa are distantly related, and different base pairs among these taxa mostly account for >2% nucleotides in the ITS regions.